Building Participatory Knowledge Infrastructure Against the GMO Agribusiness Regime: The Case of Los Campamentos Sanitarios. (19th May 2022) - Arancibia, Florencia; Arza, Valeria; Verzeñassi, Damián; Frickel, Scott
From 2010 to 2019, Argentinian medical students and faculty at the Universidad Nacional de Rosario worked with allies from grassroots movements to routinize new epidemiological data collection practices designed to call medical students' attention to the public health consequences of industrial agriculture's indiscriminate use of pesticides. This paper charts the rise and fall of their collective efforts to institutionalize participatory knowledge and pedagogy that directly challenged the political legitimacy of industrial agriculture. We anchor our study in a trio of concepts—sociotechnical regime, niche, and network—using these tools to describe the dynamic interplay among dominant and subordinate knowledge systems. Our analysis reveals that radical participatory projects cannot be understood without reference to the historical and institutional contexts that structure opportunities and constraints within which participatory knowledge research is developed, implemented, and sustained.